2011
DOI: 10.1074/jbc.m111.254177
|View full text |Cite
|
Sign up to set email alerts
|

Calpain-cleaved Type 1 Inositol 1,4,5-Trisphosphate Receptor (InsP3R1) Has InsP3-independent Gating and Disrupts Intracellular Ca2+ Homeostasis

Abstract: (8), and ischemia (9). Observations in brain ischemia models also suggest altered InsP 3 R function, specifically, decreased InsP 3 binding (10, 11), decreased InsP 3 -induced Ca 2ϩ release (12), and depletion of releasable Ca 2ϩ stores (13,14). Proteolytic cleavage of InsP 3 R could explain these observations.The type 1 InsP 3 R (InsP 3 R1), the predominant neuronal isoform, is a substrate for both the caspase and calpain families of cysteine proteases (15). These proteases are indirectly (caspase-3) and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
1
38
1
Order By: Relevance
“…7E. Previous studies showed that transient expression of the C-terminal 95-kDa-fragment resulted in a modest depletion of ER stores (22,27,30). However, examination of resting Ca 2ϩ levels and the content of intracellular Ca 2ϩ stores, as judged by the rate and magnitude of cyclopiazonic acid -induced Ca 2ϩ release, showed no significant difference between these cell lines, expressing channel-only fragments and IP 3 R1 cells or FIGURE 7.…”
Section: Characterizing Ip 3 R1 Fragmentation Patterns During Apoptosis-mentioning
confidence: 97%
See 4 more Smart Citations
“…7E. Previous studies showed that transient expression of the C-terminal 95-kDa-fragment resulted in a modest depletion of ER stores (22,27,30). However, examination of resting Ca 2ϩ levels and the content of intracellular Ca 2ϩ stores, as judged by the rate and magnitude of cyclopiazonic acid -induced Ca 2ϩ release, showed no significant difference between these cell lines, expressing channel-only fragments and IP 3 R1 cells or FIGURE 7.…”
Section: Characterizing Ip 3 R1 Fragmentation Patterns During Apoptosis-mentioning
confidence: 97%
“…Fig. 1C shows the predicted N-terminal and C-terminal fragments resulting from calpain cleavage of IP 3 R1 after glutamic acid residue 1917 (30). Finally, the membrane and soluble fragments of IP 3 R2, generated at a site corresponding to calpain cleavage of IP 3 R1, together with the epitope locations of ␣-IP 3 R2 antibodies used in this study, are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations